Historicizing the Enlightenment. - McKeon, Michael, 1943- (Bucknell University Press, 2023)
"The Enlightenment has been linked to some of the most powerfully destructive developments of modern life: imperialism, racism, capitalist exploitation, scientific absolutism, totalitarian rule; and behind these developments, the domination of facts over values, quantity over quality, the abstract over the concrete, reason over humanity, division over connection. In this two-volume collection of career-spanning essays, influential literary critic Michael McKeon argues a more complicated view by practicing a different way of doing history: imagining these oppositions as the product not of the Enlightenment but of modern experience in its maturity. These essays conjure what it was like to live through the emergence of concepts and practices that are now commonplace-society, privacy, the public, the market, secularity, democracy, human rights, sex and gender, fiction, the aesthetic attitude. Volume 1 emphasizes the revolutionary break with tradition enacted by the British Enlightenment and the effects of its inversion of traditional hierarchies. With specific focus on economics and politics, religion and society, this collection amplifies the remarkable contribution McKeon has made to the intellectual history of the Enlightenment, and is an essential addition to any collection. Published by Bucknell University Press. Distributed worldwide by Rutgers University Press"--